Plan estratégico para la empresa textil ‘‘SELVA T-SHIRTS’’ del cantón Ibarra. - Andrade, Juan P. (2021)
The purpose of this project is to carry out a Strategic Plan for the textile company "Selva T- shirts" of the canton Ibarra; In order to determine its weaknesses, strengths, opportunities,and threats in which the company develops, and thus be able to identify the critical pointsthat its operating and administrative system maintains, for this, external and internal customer evaluation matrices were carried out, an analysis at the competitive profile of the company, by evaluating internal and external factors, in order to determine the influences ofthe factors through a matrix of Offensive Strategy FO (Strengths and Opportunities), and the matrix Offensive Strategy DA (Weaknesses and Threats) that we They allowed us toestablish our strategic objectivity according to the financial perspective, client, internal process, growth and learning, and the main lines of action, starting with an organization chartthat describes each area of the company, with its goals and indicators, with a deployment of strategies that will allow the company to develop better in its environment. We propose theStrategic Plan for the textile company Selva T-Shirts in the city of Ibarra, through processesand optimization of times and resources in the development of the business line, establishing objectives and strategies both in its financial, marketing, and customer service axis., production, supply, organizational and cultural, human talent, and technology. In this way,processes will be improved avoiding wasted resources and time, consolidating a brand in themarket, improving the management of its resources and response times in a competitiveenvironment.